Private labels versus national brands: The effects of branding on sensory perceptions and purchase intentions. (November 2015) - Rossi, Patricia; Borges, Adilson; Bakpayev, Marat
Abstract: Consumers increasingly consider private labels to be as good as national brands. This research raises the question of whether national brands and private labels equally affect consumers' sensory perceptions and purchase intentions. The results of two studies show that consumers reverse their evaluation of private labels (vs. national brands) when tasting the product in an informed (vs. blind) condition. When consumers are not aware of brand names, they indicate better taste and higher purchase intentions for private labels. However, the opposite is true when they try products in an informed condition. We discuss the implications for private labels and national brands. Highlights: This research tests consumer perceptions of private labels and national brands. When consumers are aware of the brand, they prefer national brands. When consumers are blind to the brand, they prefer private labels.